PERAN IGTKI DALAM MENINGKATKAN KOMPETENSI GURU TK DI KABUPATEN TUBAN : STUDI PENGARUH PELATIHAN PROFESIONAL DAN LINGKUNGAN KERJA - Hayatun Nikmah; Ahmad Thohirin; A Faizin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the role of the Indonesian Kindergarten Teachers Association (IGTKI) in enhancing the competencies of kindergarten teachers in Tuban Regency, particularly through organizational management, professional training, and the creation of a supportive work environment. The background of this study is based on the importance of teacher professionalism as a fundamental foundation of early childhood education, as well as the demand for improving the quality of human resources in line with national educational development. As a professional organization, IGTKI plays a strategic role in fostering, coordinating, and enhancing teachers’ competencies through various continuous development programs and activities. This study employs a qualitative approach with a descriptive research design. Data were collected through observations, in-depth interviews, and documentation involving IGTKI administrators, branch administrators, and kindergarten teachers as research participants. Data analysis was conducted inductively through data reduction, data display, and meaning interpretation, while data validity was ensured through source and technique triangulation. The focus of the study is on IGTKI’s organizational management, factors influencing the improvement of teacher competencies, and the role of professional training and work environment in supporting the development of kindergarten teacher competencies in Tuban Regency.